Association Between Local Government Social Expenditures and Mortality Levels in Korea - Ko, Hansoo; Kim, Jinseob; Kim, Donggil; Kim, Saerom; Park, Yukyung; Kim, Chang-yup (Journal of preventive medicine and public health, 2013)
We examined the association between social expenditures of the local government and the mortality level in Korea, 2004 to 2010. We used social expenditure data of 230 local governments during 2004 to 2010 from the Social Expenditure Database prepared by the Korean Institute for Health and Social Affairs. Fixed effect panel data regression analysis was adopted to look for associations between social expenditures and age-standardized mortality and the premature death index. Social expenditures of local governments per capita was not significantly associated with standardized mortality but was associated with the premature death index (decline of 1.0 [for males] and 0.5 [for females] for each expenditure of 100 000 Korean won, i.e., approximately 100 US dollar). As an index of the voluntary effort of local governments, the self-managed project ratio was associated with a decline in the standardized mortality in females (decline of 0.4 for each increase of 1%). The share of health care was not significant. There were associations between social expenditures of the local government and the mortality level in Korea. In particular, social expenditures per capita were significantly associated with a decline in premature death. However, the voluntary efforts of local governments were not significantly related to the decline in premature death.